2001
DOI: 10.1114/1.1380418
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Mechanical Properties of Tracheobronchial Airways in Determining the Respiratory Resistance Time Course

Abstract: A physiologically based simulation model of breathing mechanics was considered in an attempt to interpret and explain the time course of input respiratory resistance during the breathing cycle, observed in recent studies on ventilated patients. The model assumes a flow-dependent Rohrer resistance for the upper extrathoracic airways and volume-dependent resistance and elastance for the intermediate airways. A volume-dependent resistance describes the dissipative pressure loss in the lower airways, and two const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…The second index was the absolute difference between E L at 2 Hz and E L at 0.2 Hz (E het ). Computational modeling studies (25)(26)(27)(28) have shown that the frequency dependence of E L is indicative of mechanical time constant heterogeneities in the lung. Thus, E het , as an index of frequency dependence, characterizes disease heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…The second index was the absolute difference between E L at 2 Hz and E L at 0.2 Hz (E het ). Computational modeling studies (25)(26)(27)(28) have shown that the frequency dependence of E L is indicative of mechanical time constant heterogeneities in the lung. Thus, E het , as an index of frequency dependence, characterizes disease heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…The structure-function correlates of the features were based on published anatomically consistent computational models. 1,9,22,43 Specifically, both the absolute difference between R at 0.2 Hz and R at 8 Hz and the difference between E at 2 Hz and E at 0.2 Hz are indices of frequency dependence of R and E, and thus reflect the heterogeneity of disease. It is important to note that other mechanisms such as tissue viscoelasticity and airway wall shunting can contribute to both of these absolute differences; however, we assume that the preponderance of the increase in frequency dependence is due to disease heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…where Ru is the upper airways resistance, K 1 is the resistance component for laminar flow, K 2 is the resistance component that describes turbulence andV is the flow [3] [15] [31]. The smaller inner diameters of newborn upper airways, combined with higher respiratory rates, provoke significant differences in newborn airflow behavior with respect to adults.…”
Section: Respiratory Model Adapted To the Newbornmentioning
confidence: 99%
“…the difference between intraluminal pressure of the intermediate airways and pleural pressure [3]. While this equation has been determined from adult data, similar curves, describing pulmonary pressure-volume relationships, have shown to be useful in the study of liquid ventilation in newborn lambs [35].…”
Section: Respiratory Model Adapted To the Newbornmentioning
confidence: 99%
See 1 more Smart Citation